Overview of Food Handler Sanitation Hygiene and the Presence of Bacteria Escherichia Coli on Prepared Food at Hospital X Surakarta - Wardhany, Ruthy Ayu; Maharani, Nine Elissa (Jurnal Kesehatan, 2025)
Pendahuluan: Rumah sakit X Surakarta dalam pelaksanaan higiene penjamah makanan belum terlaksana secara optimal, sesuai dengan SOP yang mewajibkan penjamah makanan menggunakan APD selama bekerja, namun kenyataannya tidak sesuai dengan standar prosedur. Bakteri E.coli adalah salah satu kontaminasi makanan yang sering ditemui, terutama akibat perilaku penjamah makanan yang tidak higienis, kontaminasi dapat menyebabkan gejala diare, muntah, kram perut, demam dan diare berdarah. Tujuan penelitian ini untuk mendeskripsikan higiene sanitasi penjamah makanan dan keberadaan bakteri E.coli pada makanan jadi di rumah sakit X Surakarta. Metode : Jenis penelitian ini deskriptif kualitatif. Populasi penelitian ini seluruh penjamah makanan yaitu 16 orang penjamah makanan dan sampel dalam penelitian ini 9 makanan jadi di Rumah Sakit X Surakarta yang dipilih secara purposive random sampling . Pengumpulan data penelitian ini menggunakan kuesioner, observasi dan pemeriksaan laboratorium. Hasil: menunjukkan bahwa 31,2% penjamah makanan di Rumah Sakit X Surakarta tidak memenuhi syarat higiene sanitasi pada Permenkes RI No. 1096/MENKES/PER/VI/2011 tentang higiene sanitasi jasaboga dan berdasarkan uji laboratorium 9 sampel makanan tidak mengandung Escherichia coli . Kesimpulan: bahwa 31,2% penjamah makanan tidak memenuhi syarat higienitas , sedangkan hasil laboratorium 100% sampel makanan jadi negatif Escherichia coli.   Introduction: Hygiene and sanitation of food handlers and food quality in hospitals are crucial for preventing the spread of disease. Although SOPs mandate that food handlers use Personal Protective Equipment (PPE) during work, the reality on the ground still does not meet established standards. E. coli is one of the most frequently encountered bacterial food contaminants. The aim of this study was to describe the sanitation hygiene of food handlers and the presence of E. coli bacteria in ready to eat food at Hospital X Surakarta. Method: This research is a quantitative descriptive study conducted in January–February 2025 at Hospital X Surakarta. The sample consisted of 16 food handlers (total sampling) and 9 processed food samples (purposive sampling). Data were collected through observation, questionnaires, and laboratory tests using the Most Probable Number (MPN) method according to SNI 2897:2008. The analysis was conducted descriptively and quantitatively based on the standards of the Indonesian Minister of Health Regulation No. 1096 of 2011. Results: The results showed that 31.2% of food handlers at Hospital X Surakarta did not meet hygiene and sanitation requirements. Based on laboratory tests, 9 food samples did not contain Escherichia coli bacteria. Conclusion: A total of 31.2% of food handlers were found not to meet hygiene requirements; however, laboratory test results showed that 100% of finished food samples were free from Escherichia coli.